Assessment of Soil Chemical Properties and Rice Yield in Tidal Submergence Ecosystem (Bangladesh Agronomy Journal, 2016)
Spatial variability of soil chemical properties is critical for improving rice productivity and sustainable farming techniques. However, a systematic assessment on the spatial variability of tidal ecosystem has not been conducted. So, 144 soil samples were collected across Barisal, Borguna and Jalkhati districts and analyzed for six common chemical properties. Rice yield data was obtained by surveying farmers during crop harvest. Soil parameters and rice yield varied considerably throughout the study areas and their coefficients of variation ranged from 8.77 to 71.04%. Slight variability was observed for soil organic matter (SOM) and available K. The pH of the soils was slightly acidic to alkaline. These paddy fields were characterized by high concentrations of SOM, available P, K and S; but low total N. Rice yield was significantly and positively correlated with pH, available K and S, but negatively correlated with SOM.Bangladesh Agron. J. 2015, 18(2): 79-87